Hepatitis B birth dose vaccination for newborns in Uganda: A qualitative inquiry on pregnant women's perceptions, barriers and preferences - Joan Nankya Mutyoba; Pamela J. Surkan; Fredrick Makumbi; Jim Aizire; Gregory D. Kirk; Ponsiano Ocama; Lynn M. Atuyambe (Elsevier, 2021)
Background: Sub-Saharan Africa continues with very low hepatitis B (HBV) birth dose vaccination coverage. To guide policy on HBV vaccine for newborns, we explored perceptions, barriers and preferences of pregnant women regarding HBV and the HBV birth dose vaccination Methods: We conducted eight focus groups discussions (FGDs) among 70 pregnant women, stratified by rural-urban residence, age and education level, using a structured focus group discussion guide to explore birth dose awareness, perceptions, barriers and preferences. Data were transcribed, coded and analysed using framework analysis. Results: Perceptions related to HBV and liver cancer causes and prevention were diverse; most FGD participants did not perceive illnesses as distinctly different. Older women-groups, both urban and rural, had never heard about HBV, but were aware of liver cancer, viewing the disease as fatal. No FGD participants were aware of HBV birth dose. Concerns included vaccine safety, its availability to women who deliver outside the health system and mistrust in health-care worker (HCWs) when handling newborns. Rural-dwelling groups perceived absence of HBV services, while FGDs with young participants believed vaccine side-effects hampered birth dose planning. Most women-groups preferred (i) oral to injectable vaccines; (ii) receiving birth dose education during antenatal, to media-based education; (iii) that newborns receive the birth dose immediately after delivery in the mother's presence. Conclusion: Although the birth dose is acceptable among pregnant women, planners need to continuously engage them as key stakeholders during planning to address concerns, in order to raise confidence, maximize uptake and strengthen HBV eradication efforts.